2019
DOI: 10.1002/cctc.201901300
|View full text |Cite
|
Sign up to set email alerts
|

The Stereoselective Formation of trans‐Cumulene through Dehalogenative Homocoupling of Alkenyl gem‐Dibromides on Cu(110)

Abstract: Stereoselective synthesis of geometrically pure isomers is challenging and important in a variety of chemistry related disciplines and applications. The recently developed on‐surface synthesis strategy provides us opportunities in the fabrication of specific nanostructures which remain challenging by conventional solution chemistry. In this work, we choose alkenyl gem‐dibromides as molecular precursors, and demonstrate the formation of specific trans‐cumulene products via C−C couplings on Cu(110). This study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…Thus, from the results discussed above, the whole scenario can be speculated below (Figure 4e): complete debromination of C 6 Br 6 should occur on the Ag(111) surface at RT, which could then result in the formation of a C 6 ring intermediate that was not stable and broken into the C 6 chain via a ringopening process and finally polymerized into the observed organometallic polyyne. According to previous studies, the surface-stabilized carbene (=C:) could directly couple into the cumulene structure without bonding to a metal adatom, 30,31 whereas the dehalogenated terminal alkynyl group (≡C•) would form organometallic structures on metal surfaces. 32,33 Therefore, the formation of C 6 −Ag organometallic polyyne implied the individual C 6 chain should be polyynic instead of cumulenic.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, from the results discussed above, the whole scenario can be speculated below (Figure 4e): complete debromination of C 6 Br 6 should occur on the Ag(111) surface at RT, which could then result in the formation of a C 6 ring intermediate that was not stable and broken into the C 6 chain via a ringopening process and finally polymerized into the observed organometallic polyyne. According to previous studies, the surface-stabilized carbene (=C:) could directly couple into the cumulene structure without bonding to a metal adatom, 30,31 whereas the dehalogenated terminal alkynyl group (≡C•) would form organometallic structures on metal surfaces. 32,33 Therefore, the formation of C 6 −Ag organometallic polyyne implied the individual C 6 chain should be polyynic instead of cumulenic.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, at the peripheral of ordered islands, another motif with a V shape (as highlighted by the green contour) is also observed (Figure d). According to our previous results obtained on the Au(111) and Cu(110) surfaces, , combined with a detailed comparison of the experimental topographies and dimensions with the corresponding simulated STM images (Figures e and S1) and the calculated adsorption models (Figure f,g), it is identified that the reaction products on Ag(111) are dimerized bBVBP molecules with trans - or cis -cumulene moieties. Such a dehalogenative C–C homocoupling reaction is depicted in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…The alkenyl gem -dibromide group, with versatile chemical reactivity, demonstrated that an elimination reaction occurs and yields terminal alkynyl bromides in solution chemistry (as shown in Scheme a), while on metal surfaces (e.g., Au(111), Cu(111), and Cu(110)), sequential dehalogenation followed by C–C homocoupling occurs with the formation of a cumulene moiety. , …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Different from radialenes, [ n ]­cumulenes ( n = the number of cumulative double bonds in a chain of n + 1 atoms) are linear carbon chains containing three or more cumulative double bonds in which all internal atoms except for the terminal two atoms are sp-hybridized carbons, endowing them with unique structural rigidity and electronic properties . With special four atom centers and six π-electrons, [3]­cumulene is the simplest cumulene system; thus, a variety of [3]­cumulene-containing systems have been explored on surfaces, where the synthetic methods mainly involve the surface-assisted dehalogenative coupling of gem -dibromides . However, 2D heteroatom-doped cumulene-based crystals on surfaces have not been reported until now because of a lack of suitable synthetic methods.…”
Section: Introductionmentioning
confidence: 99%